Editorial Review on Volume 8 Issue 2 - Magnano, Paola (Environment and Social Psychology, 2023)
The complexity of today’s society is leading to an increase in social problems. This issue (Vol. 8 No. 2) explores interpersonal, environmental, educational, and psychological problems and offers solutions and recommendations for how to address them. Additionally, the COVID-19 pandemic has a significant impact on humanity. As a result, some of the articles in this issue emphasize how the COVID-19 pandemic affects multiple aspects of our society and highlight the most recent societal difficulties. The subject of psychological health is regularly covered in this issue. Articles in this issue discuss mental health level and relationship between psychological well-being and related factors, indicating psychological well-being are affected by various factors and stressing the importance of emotion for mental health. This issue also provides an extensive discussion in terms of issues related to education, which covers students’ attitude towards education system, sustainable development goal related education, and the environmental effect on education. Morando et al.[1] explore the incidence of academic burnout, the personality’s role as predictor and the effect of protective factor like self-efficacy and self-esteem. Some of the findings in this issue are based on the opinions or remarks of others. For example, Rozman et al.[2] supplement the existing literature with new knowledge in the field of artificial intelligence and education, and a multidimensional model of the perceived usefulness of artificial intelligence in students’ perspective about emerging jobs in the Data and AI Cluster was formed. The main findings of their research are important for curricula development and stress theses implications: emphasis on teaching the meaning and importance of AI, integration of AI in coursework, strengthening quantitative skills and developing future work skills that are aligned with emerging trends in the Data and AI Cluster[2]. This issue also covers other common and popular social problems, homophobia and the effects of the COVID-19 pandemic on tourism. Studies included in this issue are interconnected by the sustainable development goal, and the impact of the goal’s accomplishment is highlighted. In other words, by concentrating on common social occurrences, the articles in this issue offer solutions to associated issues, opening the door for additional research.